Psychometric Properties of the “Alcohol Consumption Consequences Evaluation” (ACCE) Scale for Young Spanish University Students - Sancerni-Beitia, María-Dolores; Giménez-Costa, José-Antonio; Cortés-Tomás, María-Teresa (Frontiers in Psychology, 2020)
Instruments that evaluate alcohol use consequences among young people do not consider the intensive alcohol consumption pattern that is so characteristic during these ages. Some of these instruments are even ineffective in the Spanish population. Hence the interest in developing an instrument more adapted to the reality of our young people. A total of 601 university students (35.9% male and 64.1% female) from 18 to 20 years old were recruited. All of them answered a total of 77 items obtained from the review of both the scientific literature and the different scales used to measure consequences derived from alcohol consumption. In addition, they completed the AUDIT and the Timeline Followback for self-reported consumption. The data were analyzed using factor analysis and a two-parameter logistic model. ROC curve analysis was used to establish cut-off points for different risk levels of alcohol consumption distinguishing between sexes. The final 43-item scale Alcohol Consumption Consequences Evaluation (ACCE) (Evaluación de Consecuencias derivadas del Consumo de Alcohol [ECCA]) shows adequate psychometric properties: α = 0.94; unidimensionality through exploratory factor analysis (26.25% of explained variance) and confirmatory factor analysis (RMSEA = 0.39; TLI and CFI > 0.90). In addition, ROC analyses, both at a global scale and distinguishing between sexes, were able to characterize consumers with different levels of risk, obtaining areas under the curve between 0.82 and 0.88. A scale has been obtained that enables the establishment of cut-off points to distinguish between the consequences of low, moderate and high risk alcohol consumption. The clinical utility of the ACCE is highlighted by using one single instrument to perform the screening of a possible alcohol risk consumption as well as identifying the consequences that need to be worked on in the evaluated person’s or group’s intervention.